2013
DOI: 10.1080/00380768.2013.834242
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the NH2OH-HCl-HOAc method for extracting manganese and iron oxides in Japanese Andisols and other soil types in Japan

Abstract: We evaluated the validity of Tessier's method as applied to the extraction of manganese (Mn) and iron (Fe) oxides in Japanese Andisols and other soil types in Japan. Using the original Tessier's extractant mixture, 0.04 mol L −1 hydroxylamine hydrochloride in 25% acetic acid (0.04 mol L-1 NH 2 OH-HCl in 25% HOAc), we found that substantial amounts of short-range-ordered Fe oxides were not extracted from allophanic Andisol samples and that considerable amounts of total Fe oxides were not extracted from all soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was also used to extract Fe from 'amorphous oxides' and provided similar results to AOD (Chao and Zhou 1983). Qiang et al (1994) reported smaller amounts of Fe extracted by NH 2 OH-HCl than by AOD, and so did Suda et al (2013), who used a modification (NH 2 OH-HCl in acetic acid). Qiang et al (1994) explained this by incomplete reduction, hindered by SOM that covered or occluded the oxides, similar to that found for DCB (Eusterhues et al 2014a;Coward et al 2018).…”
Section: Further Extractantsmentioning
confidence: 82%
“…It was also used to extract Fe from 'amorphous oxides' and provided similar results to AOD (Chao and Zhou 1983). Qiang et al (1994) reported smaller amounts of Fe extracted by NH 2 OH-HCl than by AOD, and so did Suda et al (2013), who used a modification (NH 2 OH-HCl in acetic acid). Qiang et al (1994) explained this by incomplete reduction, hindered by SOM that covered or occluded the oxides, similar to that found for DCB (Eusterhues et al 2014a;Coward et al 2018).…”
Section: Further Extractantsmentioning
confidence: 82%